Sustainable Supply Chains for Electric Vehicle Battery Recycling: A Literature Review - Galvez-Manriquez, D; Santander-Tapia, P; Delgado-Cadena, L (Springer Nature, 2025)
The adoption of electric vehicles has emerged as an attractive solution to address climate change. However, for their sustainable adoption, end-of-life management models for electric vehicles must also be studied, especially considering the environmental impact of the batteries used in these vehicles. In this context, this study conducts a systematic literature review to analyze and understand how electric vehicle battery recovery chains have been approached from a sustainability perspective. For this purpose, a search equation has been defined with the support of bibliometric analysis software and the use of the web of science database. Then, a systematic analysis was conducted by analyzing 7 articles dealing with the topic proposed in this research. The findings show a predominant consideration of economic and environmental aspects, as well as a low consideration of social aspects of sustainability. In addition, few studies have been carried out in developing countries. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.